Isolation And Identification Of Volatile Compounds In Fresh Water Catfish (Pangasius Sutchi) - . Edison (Jurnal Teknologi dan Industri Pangan, 2000)
Volatile compounds of fresh water catfish (Pangasius sutchi) cultured in pond and cage were extracted by micro simultaneous distillation-solvent extraction (SDE), and analyzed by gas chromatography/mass spectrometry (GC/MS). A total of 28 volatile compounds of Pangastius sutchi were detected. Of these compounds, twelve were identified as aromatics, aldehyde and miscellaneous coumpounds. Catfish cultured in pond contained higher levels of the aromatic compunds as compared to thase raised in cage.Keyword : Fresh water catfish : Pangasius sutchi; Volatile compounds.